Influence of nanomaterial (Zinc Oxide) on the durability of conventional concrete (LACCEI, 2024)
This research seeks to present a nanomaterial that can provide self-cleaning property to conventional concrete, since the pollutants found in the air are also the cause of some concrete pathologies that affect its durability, such as carbonation, acid etching, and acid rain. The main objective of this research was to counteract the deterioration of concrete constructions using zinc oxide as a self-cleaning material for conventional concrete. For which, experimental tests were carried out, such as the rhodamine B test, exposure to polluting gases and the phenolphthalein test, carried out on mortar samples, and the compressive strength test, carried out on concrete specimens. Finally, the results allowed us to conclude that zinc oxide works as a photocatalytic material and gives concrete a self-cleaning property, which allows it to keep its surface free of contaminants that normally remain impregnated and damage it, in addition to being able to observe that this aggregate decreases the resistance of the concrete by a certain percentage, so it is recommended that it be used as a mortar rather than as concrete in structural elements.